Fiber asymmetric supercapacitor based on FeOOH/PPy on carbon fibers as anode electrode with high volumetric energy density for wearable applications - Gong, Xuefei (2020)
Fiber supercapacitors are promising energy storage devices for wearable applications. However, the fiber supercapacitors are currently limited by the mediocre capacitance performances due to the use of typical carbon materials as anode, sacrificing the volumetric energy density of the whole device. In addition, the inability to undergo washable cycles and poor self-discharge rate prevents the fiber-shaped supercapacitors to be a true energy textile and affects their practicability. Hence, the porous anode electrode FeOOH/PPy@CF has been firstly prepared with a high volumetric capacitance of 30.17 F cm-3, contributing to a high volumetric energy density of 2 mWh cm-3 (based on the whole encapsulated device) for a fiber asymmetric supercapacitor MnO2@CF//FeOOH/PPy@CF in PVA/LiCl. Good flexibility could be exhibited when it was woven into a glove. Desired working voltage and capacity output could be easily obtained when connecting devices in series and parallel. The encapsulated device could worked stably even after they were dipped multiple cycles in different solution and with intensive stirring water that assimilates washing cycles. The self-discharge rate can be mitigated when ionogel electrolyte ([EMIM][TFSI]/FS) was incorporated and further enhanced the energy density to 3.7 mWh/cm-3. The outstanding properties of our assembled asymmetric fiber supercapacitor device is a good candidate for practical wearable energy storage devices.